State-of-the-Art and Perspectives for Nanomaterials Combined with Nitric Oxide Donors: From Biomedical to Agricultural Applications - Pieretti, Joana C.; Pelegrino, Milena T.; Silveira, Neidiquele M. [UNESP]; Rodrigues, Maiara G.; Seabra, Amedea B. (American Chemical Society (ACS), 2024)
The free radical nitric oxide (NO) is a signaling molecule that controls several important physiological and pathophysiological processes in mammals and in plants. In humans, the biological impacts of NO include, but are not limited to, key roles in cardiovascular, neurological, immunological, respiratory, and reproductive systems. In plants, NO modulates plant growth and development with important roles in plant defense against biotic and abiotic stress conditions. However, the administration of exogenous NO donors still faces limitations, mainly due to their instability and lack of bioavailability in the biological system. Recently, the combination of nanomaterials with NO donors has been extensively explored as a promising strategy to tailor the spatiotemporal release of therapeutic amounts of NO. Nanoscience offers smart approaches to deliver NO on demand for a particular application. Although this strategy has shown promising results, the combination of NO donors with nanomaterials is still limited to scientific studies and is less explored in agricultural applications compared with biomedical research. The current review summarizes the impact of NO and NO donors in biomedical research and agricultural applications and emphasizes the recent progress in the combination of nanotechnology and NO donors. The advantages, challenges, and drawbacks of this strategy are discussed in light of inspiring research on this exciting topic, aiming to translate these innovations into clinical/practical settings.
Keywords: agricultural applications; antimicrobial; nanomedicine; nanotechnology; Nitric oxide; toxicity